ANALYZING “PLACE” IN RUSSIAN LITERATURE (SCIENCE TIME JOURNAL, 2026)
This paper explores the concept of chronotope, as theorized by Mikhail Bakhtin, is a fundamental aspect of narrative structure that transcends the boundaries of individual works. Time and space are inextricably linked, with the former serving as the foundation of narrativity and the latter providing the necessary framework for the unfolding of events. This synthesis of temporal and spatial elements is what gives rise to the distinct "genres" or "types" of stories that readers encounter. (Yu & Zhu, 2022) In the context of Russian literature, the chronotope manifests in a variety of ways, reflecting the unique cultural and historical experiences of the nation. For instance, the theme of the "historical mission" and the notion of "suffering and redemption" often feature prominently, imbuing the literary landscapes with a profound sense of purpose and moral gravity.